The Effectiveness of an Instructional Program on Nurses Knowledge and Practice Infection Control and the care of neonate - Oday Faris Washeel (University of Thi-Qar Journal of Science, 2023)
Analyze the impact of a newborn intensive care unit nurse education program on the nurses’ infection control knowledge and practice. Theoretical/Probabilistic (pre-test and post-test for the study group). Both Al-Mussawi Hospital and Bint Al-Huda Maternity Hospital in Nasiriya city housed two of Nasiriya’s pediatric hospitals for the research. A total of 50 nurses were included in the research. A questionnaire and a checklist were used to gather the data (to measure practice). Analyses of the data were carried out utilizing SPSS version 19 (SPSS). The knowledge of nurses was significantly different between the pre- and post-tests (P< 0.05). 18 (36 %) of the nurses correctly answered the sterilization definition prior to attending the training, but 47 (94 %) correctly answered the definition after attending the program. Disinfectant, per dictionary definition After attending the session, 38 (78 %) of the nurses gave the proper definition of disinfectant, compared to 14 (28 %) of the nurses gave the correct response before attending the program. Use of personal protective equipment (PPE) is considered a common precaution in neonatal intensive care units (NICUs). Before the program, the percentage of nurses who properly answered questions concerning standard precautions and the use of personal protective equipment (PPE) in NICU care was lower than the increased percentage of nurses’ answers following the course. After a pre- and post-test assessment, the mean value of nurses’ replies to the first statement (definition of sterilization) was (0.69